(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
In behavioral therapy several techniques are used, among them the role-playing and functional analysis.Role-playing is feasible to model relevant behaviors while functional analysis is used for diagnostic evalua-tion and to produce self-knowledge. However, some clinical problems have characteristics that hinder the creation of self-knowledge, without which the client may not develop the modeling of alternative repertoires. This study aims to illustrate the combination of role-playing and functional analysis as a procedure to facilitate the development of self-awareness in clients with deficits in discrimination of functional relations and interpersonal difficulties. A session was selected from a total of 12 group meetings. The main result was the increase of self-revelations and discrimination of functional relationships by customers. It is concluded that the role-playing can be an environment to teach the client to describe functional relations and produce self-knowledge when facing interpersonal problems and difficulties on the discrimination of the actual contingencies in place